Post‐relapse survival in patients with Ewing sarcoma. Issue 6 (13th January 2015) - Ferrari, Stefano; Luksch, Roberto; Hall, Kirsten Sundby; Fagioli, Franca; Prete, Arcangelo; Tamburini, Angela; Tienghi, Amelia; DiGirolamo, Stefania; Paioli, Anna; Abate, Massimo Eraldo; Podda, Marta; Cammelli, Silvia; et al.
<x xml:space="preserve">Abstract</x> Background Post‐relapse survival (PRS) was evaluated in patients with Ewing sarcoma (EWS) enrolled in chemotherapy protocols based on the use of high‐dose chemotherapy with busulfan and melfalan (HDT) as a first‐line consolidation treatment in high‐risk patients. Procedure EWS patients enrolled in ISG/SSG III and IV trials who relapsed after complete remission were included in the analysis. At recurrence, chemotherapy based on high‐dose ifosfamide was foreseen, and patients who responded but had not received HDT underwent consolidation therapy with HDT. Results Data from 107 EWS patients were included in the analysis. Median time to recurrence (RFI) was 18 months, and 45 (42%) patients had multiple sites of recurrence. Patients who had previously been treated with HDT had a significantly (P = 0.02) shorter RFI and were less likely to achieve a second complete remission (CR2). CR2 status was achieved by 42 (39%) patients. Fifty patients received high‐dose IFO (20 went to consolidation HDT). The 5‐year PRS was 19% (95% CI 11 to 27%). With CR2, the 5‐year PRS was 48% (95% CI 31 to 64%). Without CR2, median time to death was six months (range 1–45 months). According to the multivariate analysis, patients younger than 15 years, recurrence to the lung only, and RFI longer than 24 months significantly influenced the probability of PRS. Conclusions Age, pattern of recurrence, RFI, and response to second‐line chemotherapy influence post‐relapse survival in patients with recurrent Ewing sarcoma. No survival advantage was observed from chemotherapy consolidation with HDT. Pediatr Blood Cancer 2015;62:994–999. © 2015 Wiley Periodicals, Inc.